Integration of Java Programming-Based Pert and Earned Value Management Methods Based on Residential Precast Case Study to Improve Project Cost Efficiency - Citra, Zel; Wibowo, Paksi Dwiyanto; Malinda, Yosie; Pranoto, Rodliyan Yusuf; Pitaloka, Fanny (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2024)
The need for residential houses is still high for property and construction commodities. The availability of land and market prices for residential houses continue to increase yearly. Only 45.04% of Jakarta residents had a home ownership status in 2020. 2021 is the precast building mode. It is justified that precast construction structures can save 35% on construction costs and are 27.33% more reliable than ordinary concrete structures. The research examines the integration of the PERT method and earned value management (EVM) based on Java programming in residential precast case studies. The results of this study are that the implementation of the PERT method can increase the efficiency of project duration by 6%, and the implementation of the EVM method can increase project cost efficiency by 7% with the indicators Schedule Performance Index (SPI) = 1.01 (under schedule) and Cost Performance Index = 1, 07 (Under Budget)